Memory booster plant Bacopa monniera (brahmi): biotechnology and molecular aspects of bacoside biosynthesis - Vishwakarma, R. K.; Kumari, U.; Khan, B. M. (Medicinal plants - recent advances in research and development, 2016)
Bacopa monniera (Brahmi) has been used in the Ayurvedic system of medicine as a brain tonic, memory enhancer, antianxiety, cardiotonic, anticancer, anti-inflammatory, analgesic, and anticonvulsant agent since ancient times. These pharmacological properties are mainly attributed to the triterpenoid saponins present in the extracts of the plant. Biosynthesis of triterpenoid saponins starts from the isoprenoid pathway through farnesyl pyrophosphate by cyclization of 2,3-oxidosqualene, resulting in the formation of triterpenoid backbones. The plant produces relatively smaller amounts of bacosides, and to overcome this shortage, a large amount of biomass is used in the pharmaceutical preparations. Despite a wealth of medicinal importance, the molecular characterization and pathway engineering of bacoside biosynthesis in Bacopa remain unexplored. In this chapter, we have briefly discussed the research findings on in vitro plant regeneration, genetic transformation, and molecular characterization of some of the genes involved in the biosynthesis of bacosides.